Strategies of Reprimand in Spoken Jordanian Arabic: A Sociopragmatic Study - Al-Khawaldeh, Amal Naji; Rabab’ah, Ghaleb (Jordan Journal of Modern Languages & Literatures, 2024)
This study presents an exploration of reprimand strategies in Spoken Jordanian Arabic (SJA). It also explores how gender influences the use of these strategies. The data were collected from 100 Jordanian native speakers of Arabic using a DCT. The mixed method analysis revealed that the participants employed bald on record, positive politeness strategies, negative politeness, off record, and not doing the face-threating act (FTA (strategies for expressing reprimand in SJA. It was found that the participants exhibited a preference for bald on record expressions to make reprimands. The results also showed that female participants employed various strategies when reprimanding in different situations compared to males who reprimanded directly irrespective of the domain of language use. In spite of the apparent inclination to go on record when reprimanding, the participants were found to be aware of the importance of employing positive and negative politeness strategies when performing this speech act.